The SAPAS, personality traits, and personality disorder - Ball, Laura; Tully, Ruth J.; Egan, Vincent (Guilford Press, 2016)
Many argue that current categorical personality disorder (PD) classification systems should be more dimensional and consider personality traits. The present study examined whether a brief PD screening tool, the Standardized Assessment of Personality: Abbreviated Scale (SAPAS) primarily screened for traits of low emotional stability, low extraversion, and low agreeableness, rather than PD per se. A general community sample (N=237) completed the SAPAS, a personality trait measure, and the IPDE screening questionnaire. Regressions showed that the SAPAS provided substantial incremental validity over personality trait scores in predicting total IPDE scores, indicating that the SAPAS captures variance unique to PD, rather than just extremes of general disposition. The SAPAS is an empirically valid rapid PD screen for non-clinical populations, correctly identifying 78% of individuals who screen positively for PD on the IPDE. However, the SAPAS was not effective for screening Antisocial PD, limiting its utility in forensic settings.